DEVELOPMENT TECHNOLOGY OF ELECTRICALLY CONDUCTIVE HYBRID COMPOSITE COATINGS - СВІСТІЛЬНІК, Р. Ф.; ФЕДОРІВ, Т. Р.; САВЧЕНКО, Б. М.; ОСАУЛЕНКО, С. І. (Technologies and Engineering, 2023)
Purpose. Development of the technology and composition of electrically conductive polymer coatings with an adjustable electrical resistance level based on carbon based conductive components for their use in the creation of flexible heating elements. Methodology. Specific surface and volume electrical resistances were determined by the Kelvin method using a four-electrode probe. Findings. The electrical resistance of the coating largely depends on the method of its application on substrate and the type of substrate used. The roller applicator provides a monolithic multi-layer coating with a low specific volume electrical resistance. The paper substrate allows to form a defect-free coating due to the rapid absorption of the solvent and the prevention of delamination of the system due to the increase in its viscosity. However, the film substrate is more technological in the case of creating film heating elements. The thickness of the coating affects the value of the specific volumetric electrical resistance and allows to control its electrical resistance. The lowest values of electrical resistance for the created coatings were obtained in the case of the use of electrically conductive carbon black grade XC 72 in the amount of 10–20% by mass. The introduction of inert fillers into the composition allows to reduce the flammability of the coating and improve electrical conductivity by reducing the proportion of the dielectric polymer matrix and increasing percolation. Modification of the polymer matrix with a thermoset component – bakelite resin ensures obtaining a thermostable coating resistant to the action of solvents. Originality. The dependence of the specific electrical resistance of the coating on the content and type of carbon black was established. It is shown that it is possible to regulate the electrical resistance of the coating by introducing an inert mineral filler into the composition. Practical value. The impact of the coating technology on the value of its electrical resistance has been established. The dependence of the specific electrical resistance of the coating on the type of substrate is determined.